Network Forensic of Cryptocurency Miners - Arief Ikhwan Wicaksono; Rama Sahtyawan; Dedy Hariyadi (Compiler, 2022)
As reported by BSSN on August, 2022, Indonesia has traffic anomalies of 1.6 billion traffic, with 55.83% of anomaly findings containing malware and the remaining 14.99% information disclosure is another activity. Some of this data, when further analyzed based on the type of attack, falls into the categories of breaches, successes, attempts, and failures. Investigate crimes related to misuse of resources for illegal cryptocurrency mining activities. Therefore, this study should consider acquisitions from the network side as they apply to existing government agencies/institutions. This observation thereby provides information for later evidence, intruder detection, and prosecution of perpetrators who misuse resources for personal gain. As a result, the harvesting processs can obtain valuable data from routers as a digital evidence for investigating information about network attack activitiy and anomalies traffic.